FIXED POINT THEOREM FOR CONTRACTIVE TYPE MAPPING IN DISLOCATED METRIC SPACE (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
The objective of this paper is to obtain some fixed point theorem for Dislocated metric space for generalized contraction mappings.